BUSINESS INTELLIGENCE AS AN INTEGRATION TOOL FOR FAULT DETECTION OF THE BOARD ASSEMBLY PROCESS - Paixão, Elisete da Silva; Campos, Paola Souto; Alves, Hellen Lima Leite (Seven Editora, 2025)
The plate assembly process in the company in question has a stipulated goal of 2000 plates per day, and 10% of this production has failures in the process, bringing a compromise to the goals defined by management. In view of this problem, the present study aims to implement an intelligent system for identifying and correcting failures in the process of board assembly, based on Business Intelligence, aiming at the evolution of Industry 4.0 practices. The methodology was based on Process Mapping, Analysis of Requirements for Implementation of the Integrated System. The integrated system allowed communication with other systems in the production process more quickly and effectively, bringing the most assertive information possible for the performance of usability and data security. The implementation of an intelligent system for detecting and correcting failures in the board assembly process, with the support of Business Intelligence tools, represented a significant step towards the evolution of Industry 4.0 practices.DOI: https://doi.org/10.56238/sevened2024.037-148